Social Construction and Evolutionary Perspectives on Gender Differences in Post-traumatic Distress: The Case of Status Loss Events - Azoulay, Roy; Gilboa-Schechtman, Eva (Frontiers in Psychiatry, 2022)
Women report greater post-traumatic distress than men following physically threatening events. However, gender differences in post-traumatic distress following social stressors such as status losses are understudied. Whereas the social construction account points to a general sensitivity in women following any type of stressor, the evolutionary account suggests enhanced sensitivity to status losses in men, especially following inter-males aggressions. These propositions were examined in two studies (Study 1, N=211; Study 2, N=436). Participants were asked to recall a status loss and to fill out measures assessing post-traumatic distress and depression severity. In line with the evolutionary account, men, as compared to women, displayed enhanced post-traumatic distress following status loss. Status losses conducted by men against men were associated with greater post-traumatic distress than were instances involving other target-aggressor pairings. Finally, age was negatively associated with post-traumatic distress in men but not in women. The examination of evolutionary challenges modifies the standard view linking the female gender to enhanced sensitivity to trauma. Thus, the pattern of enhanced sensitivity to stressful events appears to be affected by gender- and development-specific adaptive challenges.